2017
DOI: 10.1038/s41467-017-02187-8
|View full text |Cite
|
Sign up to set email alerts
|

Ezh2 phosphorylation state determines its capacity to maintain CD8+ T memory precursors for antitumor immunity

Abstract: Memory T cells sustain effector T-cell production while self-renewing in reaction to persistent antigen; yet, excessive expansion reduces memory potential and impairs antitumor immunity. Epigenetic mechanisms are thought to be important for balancing effector and memory differentiation; however, the epigenetic regulator(s) underpinning this process remains unknown. Herein, we show that the histone methyltransferase Ezh2 controls CD8+ T memory precursor formation and antitumor activity. Ezh2 activates Id3 while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
114
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(119 citation statements)
references
References 69 publications
(109 reference statements)
4
114
1
Order By: Relevance
“…NAD + is a regulator of Sirtuin1 (SIRT1), which has deacetylase activity (Aksoy et al, 2006) in T cells (Jeng et al, 2018), cancer cells (Chatterjee et al, 2018), and adipocytes (Cantó and Auwerx, 2012) because SIRT1 binds NAD + to deacetylate targets (Sauve et al, 2006). One of the molecules, which is deacetylated by SIRT1, is EZH2 (Wan et al, 2015), which modulates epigenetically the expression of several molecules including T-bet, RUNX3, and EOMES by trimethylating histone 3 at lysine 27 (H3K27me3) (Fujii et al, 2008;He et al, 2017;Tong et al, 2014). It has been reported that SIRT1 regulates the activity and stability of EZH2 by acetylating it at lysine 348 in HEK293T cells (Wan et al, 2015).…”
Section: Cd8cd38 High T Cells Express Low Levels Of Cytotoxic-relatedmentioning
confidence: 99%
“…NAD + is a regulator of Sirtuin1 (SIRT1), which has deacetylase activity (Aksoy et al, 2006) in T cells (Jeng et al, 2018), cancer cells (Chatterjee et al, 2018), and adipocytes (Cantó and Auwerx, 2012) because SIRT1 binds NAD + to deacetylate targets (Sauve et al, 2006). One of the molecules, which is deacetylated by SIRT1, is EZH2 (Wan et al, 2015), which modulates epigenetically the expression of several molecules including T-bet, RUNX3, and EOMES by trimethylating histone 3 at lysine 27 (H3K27me3) (Fujii et al, 2008;He et al, 2017;Tong et al, 2014). It has been reported that SIRT1 regulates the activity and stability of EZH2 by acetylating it at lysine 348 in HEK293T cells (Wan et al, 2015).…”
Section: Cd8cd38 High T Cells Express Low Levels Of Cytotoxic-relatedmentioning
confidence: 99%
“…For example, transcription of EZH2 (the core subunit of PRC2) is up-regulated following TCR co-stimulation, peaks at ~1 day post-infection, and is largely back to basal levels by day 7 post-infection 30 . At the protein level, PRC2 activity peaks around 3-5 days postinfection 41,42 , at which time EZH2/PRC2 suppress the already active pro-memory/proliferation genes FOXO1 and TCF-1 while suppressing the pro-effector/exhaustion gene EOMES ( Fig. 7 and Fig.…”
Section: The 2-state Tce Model Allows Prediction Of Drug Effectsmentioning
confidence: 99%
“…T cell differentiation is intimately linked to epigenetic programming, but the mechanistic role of epigenetic marks in steering T cell differentiation 40,60,61,63,69,70 and thymic selection [71][72][73][74][75] has only recently become more clear. Here we observed that ablation of Dot1L in the T cell lineage differentially affected CD4 + and CD8 + T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Sets of differentially expressed genes in indicated conditions were called 'gene signatures'. An exception was made for the Ezh2 RNA-Seq data from He et al, 61 wherein the dispersion was estimated with a local fit, using `estimateDispersion` function in DESeq2 with the argument `fitType = "local"` and using an adjusted pvalue cutoff of 0.05, to increase the number of detected differential genes. Principal component analysis was performed using the `prcomp` function on variance stabilizing transformed data of all samples with the `vst` function from the DESeq2 package on all samples using default arguments.…”
Section: Rna-seq Data Preprocessingmentioning
confidence: 99%
See 1 more Smart Citation